2022
DOI: 10.3390/nu14214621
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Caucasian Seniors on the Rise: Is It Truly Harmful? Results of the PolSenior2 Study

Abstract: Obesity is associated with an increased risk of morbidity and mortality; however, data suggest that in old age, obesity is not detrimental. The study’s objective was to verify whether obesity frequency still increases in Polish Caucasian seniors and to verify the “obesity paradox”. Five thousand and fifty-seven community-dwelling individuals aged ≥ 65 years completed a detailed medical questionnaire, underwent measurements of the body mass index (BMI) and the waist circumference (WC), and an evaluation of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Several previous studies have suggested that BMI may be a protective factor against ADL impairment, 34–36 leading to the ‘obesity paradox’. However, using BMI as an indicator standard for obesity makes it difficult to reflect the effects of fat and muscle content, 37 leading to the biased conclusion that obesity facilitates the maintenance of better functional capacity (BADL/IADL).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested that BMI may be a protective factor against ADL impairment, 34–36 leading to the ‘obesity paradox’. However, using BMI as an indicator standard for obesity makes it difficult to reflect the effects of fat and muscle content, 37 leading to the biased conclusion that obesity facilitates the maintenance of better functional capacity (BADL/IADL).…”
Section: Discussionmentioning
confidence: 99%
“…6 Obesity paradox has been termed although people who are overweight or obese are likely to develop heart diseases, once a person has established heart condition, those with higher BMI appeared to have better prognosis, which is eminent in old adults and patients with heart failure. 7 Skeletal muscle mass (SMM) has been indicated to be the key that explains the heterogenous cardiovascular effects of weight loss, especially the dynamic change in muscle mass along with weight change (WC). [8][9][10] Several studies have suggested that sarcopenia and obesity sarcopenia are detrimental to cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%
“…Weight management in overweight/obesity old adults has been discussed for decades due to the pandemic of obesity and aging 6 . Obesity paradox has been termed although people who are overweight or obese are likely to develop heart diseases, once a person has established heart condition, those with higher BMI appeared to have better prognosis, which is eminent in old adults and patients with heart failure 7 . Skeletal muscle mass (SMM) has been indicated to be the key that explains the heterogenous cardiovascular effects of weight loss, especially the dynamic change in muscle mass along with weight change (WC) 8–10 .…”
Section: Introductionmentioning
confidence: 99%